Cord Blood Extracellular Vesicles Analyzed by Flow Cytometry with Thresholding Using 405 nm or 488 nm Laser Leads to Concurrent Results - Pekárková, Kristýna; Soukup, Jakub; Kostelanská, Marie; Širc, Jan; Straňák, Zbyněk; Holada, Karel (Diagnostics (Basel, Switzerland), 2021)
Extracellular vesicles (EVs) from liquid biopsies are extensively analyzed by flow cytometry, a technology that is continuously evolving. Thresholding utilizing a violet 405 nm laser side scatter (VSSC) has recently been implemented. Here, we collected set of large EV (lEV) samples from cord blood, which we analyzed using a standard flow cytometer improved via a 405 nm laser side scatter. Samples were analyzed using two distinct thresholding methods-one based on VSSC, and one based on VSSC combined with fluorescence thresholding on stained phosphatidylserine. Through these thresholding methods, we compared lEVs from pre-term births and control cord blood. Double-labeled lEVs with platelet CD36+/CD41+, activated platelet CD41+/CD62P+ and endothelial CD31+/CD105+ antibodies were used. Apart from comparing the two groups together, we also correlated measured lEVs with the thresholding methods. We also correlated the results of this study with data analyzed in our previous study in which we used a conventional 488 nm laser SSC. We did not find any difference between the two cord blood groups. However, we found highly concurrent data via our correlation of the thresholding methods, with correlation coefficients ranging from 0.80 to 0.96 even though the numbers of detected lEVs differed between thresholding methods. In conclusion, our approaches to thresholding provided concurrent data and it seems that improving the cytometer with the use of a VSSC increases its sensitivity, despite not being particularly critical to the validity of flow cytometric studies that compare pathological and physiological conditions in liquid biopsies.
Keywords: extracellular vesicles; data correlation; thresholding parameter; flow cytometry